1988
DOI: 10.1073/pnas.85.21.7897
|View full text |Cite
|
Sign up to set email alerts
|

Role of disulfide bridges in determining the biological activity of interleukin 3.

Abstract: Total chemical synthesis of analog proteins was used to examine the requirement for specific disulfide bridges for the biological activity of interleukin 3 (IL-3), a growth factor that stimulates multiple lineages of hemopoietic cells. Four structural analogs of the mature, 140 amino acid murine IL-3 molecule were synthesized in which specific cysteine residues were replaced by alanines. In a quantitative IL-3 assay, based on [3H~thymidine incorporation into factordependent cells, the IL-3 analog with alanines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…(48). In addition to 26% amino acid identity and 40% homology based on conservative substitutions, the biologically critical disulfide bond of IL-3 is conserved throughout evolution ( 18,25 ). Furthermore, Pakula and Sauer have recently shown that surface side chain changes have little impact on the tertiary structure ofpolypeptides (49).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(48). In addition to 26% amino acid identity and 40% homology based on conservative substitutions, the biologically critical disulfide bond of IL-3 is conserved throughout evolution ( 18,25 ). Furthermore, Pakula and Sauer have recently shown that surface side chain changes have little impact on the tertiary structure ofpolypeptides (49).…”
Section: Methodsmentioning
confidence: 99%
“…Initial studies using truncated synthetic polypeptides of murine IL-3 suggested that the first disulfide bond and the amino-terminal half ofthe molecule are responsible for biological activity (17,18). Recently, two groups have reported on the binding sites ofneutralizing mAbs of human IL-3 (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Helices were then packed by using the combinatorial packing algorithm of Cohen et al (20). The resulting structures were screened for compactness and consistency by using known disulfide constraints (21,22) and a preference for antiparallel helices.…”
mentioning
confidence: 99%
“…A distance of 2.5 Å between the side chain nitrogen of Lys 28 and one of the carboxyl oxygen atoms of Glu 366 in this model suggests a salt bridge between Lys 28 of IL-3 and Glu 366 of the ␤ subunit. Although this interaction may facilitate the proper docking of the ligand, its contribution to the overall binding energy is relatively small considering the 2-4-fold decrease in binding affinity when this potential interaction was disrupted by the E366A mutant of the ␤ subunit (29) or by the K28E mutant of IL-3 (20).…”
mentioning
confidence: 99%